Lithogeochemical characteristics and potential hyperaccumulator identification as phytomining agent at the Ratatotok gold mine, Indonesia - Aminatun, Tien; Idrus, Arifudin; Simbolon, Doly; Rakhmawati, Anna; Atun, Sri (Journal of Degraded and Mining Lands Management, 2024)
In the future, phytomining will be an environmentally friendly alternative mining technology. Therefore, the exploration of vegetation types having the potential as hyperaccumulators in gold phytomining needs to be carried out. This study aimed to (1) investigate the effect of rock/soil mineralogy characteristics and Au content on the diversity of vegetation types at gold mine sites, and (2) determine the type of potential hyperaccumulator vegetation as a phytomining agent based on the Biological Concentration Factor (BCF). This study was conducted at the Ratatotok gold mine in North Sulawesi Province, Indonesia. The sampling locations consisted of 3 sites, i.e., Bulex, Yance, and Leon, and each site consisted of 5 sampling plots. Soil samples were taken from each sampling plot and then tested for gold content using the ICP-MS method and mineral content using the XRD method. Mineralized bedrock samples were also taken for mineralogical analysis through petrography. Data analysis of soil geochemistry was carried out descriptively. Quantitative descriptive analysis was also carried out to determine the dominant type of vegetation, which was potential for hyperaccumulators at the mine site. The results showed that gold content in the soil affected the diversity of vegetation, which was possibly due to gold stress, which affected plant growth. Based on the BCF value, three local plant species having potential as gold hyperaccumulators with moderate bioaccumulation ability (BCF>0.1-1) were found, namely Pteris vittata, Syzygium aromaticum, and Swietenia mahagoni. However, the use of these plants as phytomining agents requires further research.